Exploring the lived experiences of participants and facilitators of an online mindfulness program during COVID-19: a phenomenological study - Melvin, Ashley; Canning, Christopher; Chowdhury, Fariha; Hunter, Sarah; Kim, Soyeon (Frontiers in Public Health, 2023)
The coronavirus pandemic (COVID-19) has placed incredible demands on healthcare workers (HCWs) and adversely impacted their well-being. Throughout the pandemic, organizations have sought to implement brief and flexible mental health interventions to better support employees. Few studies have explored HCWs’ lived experiences of participating in brief, online mindfulness programming during the pandemic using qualitative methodologies. To address this gap, we conducted semi-structured interviews with HCWs and program facilitators (n = 13) who participated in an online, four-week, mindfulness-based intervention program. The goals of this study were to: (1) understand how participants experienced work during the pandemic; (2) understand how the rapid switch to online life impacted program delivery and how participants experienced the mindfulness program; and (3) describe the role of the mindfulness program in supporting participants’ mental health and well-being. We utilized interpretive phenomenological analysis (IPA) to elucidate participants’ and facilitators’ rich and meaningful lived experiences and identified patterns of experiences through a cross-case analysis. This resulted in four main themes: (1) changing environments; (2) snowball of emotions; (3) connection and disconnection; and (4) striving for resilience. Findings from this study highlight strategies for organizations to create and support wellness programs for HCWs in times of public health crises. These include improving social connection in virtual care settings, providing professional development and technology training for HCWs to adapt to rapid environmental changes, and recognizing the difference between emotions and emotional states in HCWs involved in mindfulness-based programs.